The Role of Islamic Loans in Advancing Financial Inclusion and Socio-Economic Development - Ramzi Abdullah Ahmed Hassan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study explores the role of loans in Islam in fostering financial inclusion and addressing various economic and social challenges, particularly in Muslim-majority countries. By adopting a comparative research methodology, the research evaluates how Islamic loans differ from conventional financial instruments in promoting inclusive economic growth, alleviating poverty, and supporting community development. It investigates the challenges of Islamic loans, including accessibility, regulatory constraints, and cultural perceptions, while also exploring the potential benefits and limitations. Additionally, the study highlights the significant role of Islamic financial literacy in enhancing financial inclusion, focusing on how well-informed communities can better utilize Islamic financial services. The paper underscores the importance of Islamic finance, including tools like microfinance, zakat, and risk-sharing contracts, in contributing to poverty reduction, wealth redistribution, and overall economic stability. Through this analysis, the study presents a comprehensive understanding of how Islamic finance can serve as a powerful tool for sustainable economic development and financial inclusion.